PENGARUH BEBAN SIKLIS PADA TANAH LEMPUNG KENYANG AIR DALAM TINJAUAN PARAMETER DINAMIS TANAH - , SERCI ARITA NEOLAKA,S.Pd; , Prof (ret). Dr. Ir. Kabul Basah Suryolelono, Dip. H.E., D.E.A., ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Dynamic loading in saturated clay has an effect to weaken the bounding of soil particles, so that the soil stiffness and shear strength decreases. The condition will effect instability of structure, even collapsed, which in turn causes both material and non-material losses. Both shear modulus and material damping ratio are the important dynamic parameters of soil as a key parameters in design procces. The objective of the research is to find out the behavior of shear modulus, damping ratio, and hysteretic loop of saturated clay under dynamic loading. In the research, laboratory tests were done using cyclic tryaxial with variation in factors affecting both material damping ratio and shear modulus, including variation in deviatoryc stress and loading frequency. Confining stress applied on the sample was 50 kPa. The type of testing selected was cyclic modulus and damping test in accordance with the ASTM D3999-91 in 2007. Result of the research showed that with the increase of axial stress applied, the value of material damping ratio of soil increased, shear modulus decreased and the graphic of hysteretic loop tended to be more symmetrical in the application of larger deviatoryc stress and tended to be more flat. Such condition describes that the larger the dynamic load in the saturated clay, the lower of soil stifness and shear strength of soil. Result of the research indicates that with the increase of loading frequency applied, the higher value of shear modulus and material damping ratio. It describes that the longer the period of dynamic loading applied, the lower of soil stiffness and shear strength of soil. Test result of the research showed that the value of shear modulus range are 141,379 MPa to 299,172 MPa and the value of material damping ratio range are 0,467% to 2,674% and the shear strain range are 0,001% to 0,0032%.